UMKM Go Digital: Optimalisasi Teknologi Multimedia dalam Meningkatkan Kompetensi Pemasaran Digital UMKM di Era 4.0 - SIGIT SETIYANTO; AISYAH MUTIA DAWIS (Indonesian Journal of Business Intelligence (IJUBI), 2024)
The Industry 4.0 revolution demands that MSMEs (Micro, Small and Medium Enterprises) adapt to digital transformation, especially in marketing. The research aims to study the optimization of multimedia technologies, including augmented reality (AR), to enhance the digital marketing competence of MSMEs of Surakarta City in this era. The research uses a mixed method approach, combining surveys, interviews, and case studies. The results of the research show that the use of multimedia technology, including AR, contributes significantly to the enhancement of digital marketing competence of MSMEs of Surakarta City. Black box testing on the website showed a 100% success rate on all major functions, proving the effectiveness of this technology. Interesting and interactive multimedia content has proven to increase product visibility, broaden market reach, and encourage consumer interaction. AR enables a more in-depth and informative shopping experience, enhancing confidence and buying decisions. It is recommended that MSMEs of Surakarta City be given training and technology infrastructure support to optimize the use of multimedia technology. Collaboration with technology experts and the use of social media are also important strategies. This research provides a foundation for the development of MSMEs marketing strategies that are more effective in the 4.0 era of Surakarta City.